Educator Perceptions of Early Learning Environments as Places for Privileging Social Justice in Rural and Remote Communities - Vicki Christopher; Michelle Turner; Nicole C. Green (MDPI AG, 2022)
Early childhood education and care (ECEC) in Australia has long been associated with the concept of social justice, however, a clear understanding of what it looks like across diverse services and communities is not available. This article reports the process of inquiry, as well as the outcomes, of a small-scale study designed to uncover the perceptions of ECEC educators working in rural and remote communities in the state of Queensland. Data were collected through individual semi-structured interviews with five educators from rural and remote settings identified as areas experiencing significant growth in population diversity. An initial thematic analysis of the data revealed three key themes. A secondary analysis using a place and space conceptual framework uncovered deeper, more sophisticated meanings of the educator experience of social justice. The research is important in bringing pedagogical conversations to the forefront regarding ECEC educator perceptions of their role in creating a socially just learning environment. In addition to identifying future research possibilities, implications from the findings indicate opportunities for re-examining and rethinking initial teacher education and ongoing professional learning.